Emergence of Usutu virus in Hungary - Bakonyi, Tamás; Erdélyi, Károly; Ursu, Krisztina; Ferenczi, Emoke; Csörgo, Tibor; Lussy, Helga; Chvala, Sonja; Bukovsky, Christiane; Meister, Tanja; Weissenböck, Herbert; Nowotny, Norbert (Journal of clinical microbiology, 2007)
In 2001, Usutu virus (USUV), a mosquito-borne flavivirus of the Japanese encephalitis virus serogroup related to West Nile virus and previously restricted to sub-Saharan Africa, emerged in wild and zoo birds in and around Vienna, Austria. In order to monitor the spread of the infection, a dead bird surveillance program was established in Austria and in neighboring Hungary. In Hungary, 332 dead birds belonging to 52 species were tested for USUV infection between 2003 and 2006. In the first 2 years, all birds investigated were negative. In August 2005, however, USUV was detected in organ samples of a blackbird (Turdus merula), which was found dead in Budapest, Hungary, by reverse transcription-PCR, immunohistochemistry, and in situ hybridization. In July and August 2006, a further six dead blackbirds tested positive for USUV, and the virus was isolated from organ samples of one bird. These birds were also found in urban areas of Budapest. The nearly complete genomic sequence of one Hungarian USUV strain was determined; it was found to share 99.9% identity with the strain that has been circulating in Austria since 2001. This result indicates that the USUV strain responsible for the blackbird die-off in Budapest most likely spread from Austria to Hungary instead of being independently introduced from Africa.